In the middle with hat and beard Landauer before the prison in Starnberg May 1. From the correspondence of Raphael Friedeberg with Nettlau (1919)
In the middle with hat and beard Landauer before the prison in Starnberg May 1. From the correspondence of Raphael Friedeberg with Nettlau.